Microbiota of dental caries in primary teeth of a costa rican child population = Microbiota de la caries dental en piezas primarias de una población infantil costarricense - Tenorio Soto, Keysy 1990-
The objective of this research was to identify bacteria present in the microbiota of dentinal carious lesions in primary molars of some Costa Rican pediatric patients. Data were collected from 15 children aged between 4 and 8 years old who attended the Pediatric Dentistry Clinic at the Faculty of Dentistry from the University of Costa Rica (UCR). The inclusion criteria were: infants between 4 and 8 years old who presented cavitated carious lesions in primary teeth, who were actively attended by students at the Faculty of Dentistry from the UCR, and whose parents or legal guardians signed the informed consent to participate in this research. Samples were taken using a sterile spoon, placed in storage vials, and subjected to various conventional and molecular microbial identification techniques, such as Gram stain identification, catalase tests, oxidase, TSI, API 20E, API STAPH, and VITEK 2. Of the 60 bacterial strains subjected to Gram staining, the following was obtained: 28 Gram-positive bacteria and 32 Gram-negative bacteria. The main isolated organisms were species of Staphylococcus epidermidis, Pasteurella pneumotropica/Mannheimia haemolytica, Pantoea spp, and Streptococcus mutans.